Local History and Cultural Heritage in 21st-Century History Education: A Systematic Review of Pedagogy, Skills, and Sustainability - Tomy Wijaya; Fatimah Alauwiyah; Muhammad Reza Pahlevi (MASI Mandiri Edukasi, 2026)
This study presents a systematic literature review on the integration of local history and cultural heritage in 21st-century history education, focusing on pedagogical models, competency development, and alignment with Sustainable Development Goal (SDG) 11. Guided by the PRISMA 2020 framework, the review synthesizes 17 peer-reviewed and indexed articles published between 2020 and 2025. Thematic analysis was employed to map dominant instructional approaches, learning outcomes, and persistent research gaps. The findings indicate that heritage-based history education is implemented through place-based learning, heritage inquiry, museum and community engagement, and digital pedagogy such as virtual reality and virtual field trips, all of which significantly strengthen historical thinking and broader 21st-century skills, particularly critical thinking, collaboration, and digital literacy. The review further confirms a conceptual linkage between heritage-based history education and SDG 11 in fostering sustainability awareness, cultural preservation, and community participation. Nevertheless, the literature reveals fragmented curricular integration, limited longitudinal evidence on competency development, and insufficient systematic evaluation of the measurable contribution of history education to sustainability outcomes. By integrating pedagogical models, competency frameworks, and sustainability objectives within a unified analytical perspective, this study provides a structured conceptual foundation for advancing heritage-based history education in contemporary formal learning contexts.